TEACHING ENGLISH THROUGH PRAGMATIC COMPETENCE - Sa’dullayeva , Sabina (Innovative Development in Educational Activities, 2024)
Teaching English as a second language (TESL) has evolved significantly over the years, with a growing emphasis on communicative competence. Pragmatic competence, a crucial aspect of communication, has gained attention for its role in enabling learners to use language appropriately in various social contexts. This article explores the importance of pragmatic competence in English language teaching and provides strategies for educators to integrate pragmatic instruction into their pedagogical practices.